Cardiac Expression of Tnnt1 Requires the GATA4-FOG2 Transcription Complex - Nikolay L. Manuylov; Sergei G. Tevosian (The Scientific World Journal)
Previous work by us and others has shown that the loss of interaction between GATA4 and FOG2 protein partners is embryonic lethal due to heart failure at embryonic day (E) 13.5; however, the role of this important protein duo in various cardiac compartments (e.g., myocardial, endocardial, or epicardial cells) remains to be understood. Although a dual role (both as an activator and a repressor) for the GATA4-FOG2 transcriptional complex has been put forward, the specific genes under GATA4-FOG2 control in the developing heart have remained largely elusive. Since the myocardial-restricted Fog2 re-expression in the Fog2 null embryos is sufficient to extend their life span, identification of GATA4-FOG2 target genes in cardiomyocytes could shed light on the molecular mechanism of GATA4-FOG2 action in these cells. We report here that cardiac expression of slow skeletal troponin T (Tnnt1) strictly depends on the physical interaction between GATA4-FOG2 in the myocardium of both atria and ventricles.